2020
DOI: 10.1002/app.49762
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and mechanical behaviors of rigid organic particles reinforced polycarbonate

Abstract: For the purpose of promoting mechanical properties of bisphenol-A polycarbonate (PC) reinforced by rigid organic styrene-acrylonitrile copolymer (SAN) particles, styrene/acrylonitrile/glycidyl methacrylate terpolymer (SAG) was synthesized and applied as compatibilizer for PC/SAN blends. It is found that the phase morphology of PC/SAN/SAG blends is closely related with their mechanical properties. Large continuously distributed SAN phase or spherical dispersed SAN particles with average diameter over 2 μm tend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…To date, many researches have shown that organic particles have several distinct modes to toughen the brittle polymer matrix 51,52 . Some important factors are also related to the fracture behavior of particle‐polymer composites such as particle‐matrix interface bonding strength, particle size and volume fraction, particle modulus and ductility 53 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, many researches have shown that organic particles have several distinct modes to toughen the brittle polymer matrix 51,52 . Some important factors are also related to the fracture behavior of particle‐polymer composites such as particle‐matrix interface bonding strength, particle size and volume fraction, particle modulus and ductility 53 .…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly important for the polymers, such as EP, PET, PC, PU, UP etc. that do not experience a free‐radical pyrolysis process 159–162 . In particular, free radical capturers can be designed by integrating the gas and condensed phase mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…that do not experience a free-radical pyrolysis process. [159][160][161][162] In particular, free radical capturers can be designed by integrating the gas and condensed phase mechanisms. For example, regarding EP and polyesters, the scavengers are more efficient for the LOI and UL-94 tests but will only lead to limited heat release reductions.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the microstructure morphology of the nanocomposite, a scanning electron microscope (SEM, S-4700, Hitach, Tokyo, Japan) was used to observe the dispersion of nanoparticles in the sample. The thermal properties of the samples were measured using differential scanning calorimetry (DSC, Q2000 system, TA instrument, New Castle, DE, USA) [21][22][23][24][25][26]. Stopping and range of ions in matter (SRIM) simulation was performed to estimate the thickness of the ion beam penetration into the composite, and ion beam injection was performed at different flow rates/energies using two ion species (N and Cr) at room temperature.…”
Section: Methodsmentioning
confidence: 99%